The quality of threat in modern painting - Radford, Anne Margaret (Rhodes University, Faculty of Humanities, Department of Fine Art, 1979)
From Introduction: We not only tolerate violence, we put it on the front pages of our newspapers. One-third or one-fourth of our television programmes use it for the amusement of our children. Condone! My dear friends, we love it." -Karl Menninger, psychiatrist. War is one of the most violent of man's past-times, yet many of the atrocities committed are termed heroic deeds. Andre Malraux, one of the leading writer-philosophers of his day, praised the international involvement by so many writers, artists, etc. in the Spanish Civil War as one of the most wonderful deeds of brotherhood in the history of mankind. There is a strange idolatry that is often accorded to violent criminals such as the early American outlaws, and people like Charles Manson, around whom an entire cult has sprung up. The "aggressive machismo" is something that boys and young men strive to achieve in most countries in the Western world. Scientlsts and philosophers have puzzled these paradoxes for centuries, and this effort to unravel the mystery of violence and aggression bears a fateful significant. For the quality of human life and the survival of man are involved. Robbery, rape, riots, vandalism, are all now part of man's existence. Around the world, violence has soared. In London, violent crimes increased by 39 per cent in three years. Even sports events (the soccer fans stage gang wars at most soccer matches nowadays, especially in England,) and entertainment ---books, movies, television--- have become permeated with violence. It has not always been as bad as this, and as art imitates life, life imitates art, and so aggressive paintings, threatening paintings are now commonplace. In this dissertation, I have studied this development of threat in painting. What follows is the course my study has taken.
Keywords: Painting, Modern -- 20th century